Sobre restaurar fios: reflexões sobre a pobreza em A hora da estrela - Ivana Ferrante Rebello (Estudos de Literatura Brasileira Contemporânea)
This article reads the novel A hora da estrela, by Clarice Lispector, through the lens of poverty. The story of a poor northeast girl and without success in life is an anguished and self-reflective narrative. The job of darning and typing are metaphors of the tension of the author. The novel about poverty brings into the scene theimpotence of writing about the events.